2018
DOI: 10.2337/db18-0955
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glucocorticoid Suppression of TGFβ Signaling in Human Omental Adipose Tissues Limits Adipogenesis and May Promote Fibrosis

Abstract: Visceral obesity is associated with insulin resistance and higher risk of type 2 diabetes and metabolic diseases. A limited ability of adipose tissues to remodel through the recruitment and differentiation of adipose stem cells (ASCs) is associated with adipose tissue inflammation and fibrosis and the metabolic syndrome. We show that the lower adipogenesis of omental (Om) compared with abdominal subcutaneous (Abdsc) ASCs was associated with greater secretion of TGFβ ligands that acted in an autocrine/paracrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Among co-receptors, only betaglycan (a.k.a. TGFβR3) was highly expressed, highlighting its recently described role in adipogenesis (Lee et al, 2019). The SMAD2/3 pathway activating ligands TGF-β1, TGF-β2, and Activin A were also significantly expressed.…”
Section: Distinct Expression Of Tgf-β Family Receptors and Ligands Inmentioning
confidence: 81%
See 1 more Smart Citation
“…Among co-receptors, only betaglycan (a.k.a. TGFβR3) was highly expressed, highlighting its recently described role in adipogenesis (Lee et al, 2019). The SMAD2/3 pathway activating ligands TGF-β1, TGF-β2, and Activin A were also significantly expressed.…”
Section: Distinct Expression Of Tgf-β Family Receptors and Ligands Inmentioning
confidence: 81%
“…Transforming Growth Factor-β (TGF-β) family ligands, which include TGF-β, Activin, GDF, and BMP family growth factors, have known roles in both adipogenesis and adipocyte hypertrophy (Lee, 2018, Tang & Lane, 2012, Zamani & Brown, 2011. Thus, TGF-β1, GDF-8, and Activins A and B inhibit adipogenesis (Choy, Skillington et al, 2000, Hirai, Yamanaka et al, 2005, Hoggard, Cruickshank et al, 2009, Ignotz & Massague, 1985, Kim, Liang et al, 2001, Lee, Pickering et al, 2019, Luo, Guo et al, 2019, Sparks, Allen et al, 1992, whereas several BMPs have been shown to promote adipogenesis and/or adipocyte hypertrophy (Gustafson, Hammarstedt et al, 2015, Huang, Song et al, 2009, Modica & Wolfrum, 2017, Schreiber, Dorpholz et al, 2017, Tang, Otto et al, 2004, Tseng, Kokkotou et al, 2008. Yet in spite of a large body of work in this area, fundamental questions remain unresolved, including what steps of adipogenesis are regulated by specific TGF-β family pathways, how are intracellular signaling pathways activated to direct adipocyte development, and can extracellular TGF-β family inhibitors help control adipogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, TGF-β1 impairs corticosteroid action. Corticosteroids were not effective in modulating fibrotic processes that leads to remodeling [23,[30][31][32]. To confirm this phenomenon, we treated MRC-5 cells with either TGF-β1 or IL-4/IL-13 and incubated with dexamethasone.…”
Section: Aitc Significantly Improved Dexamethasone Insensitivitymentioning
confidence: 98%
“…GATA6‐expressing LPMs are an important source of TGF‐β 19 . Importantly, TGF‐β suppresses adipogenesis by activating the transcription factor, mothers against decapentaplegic homolog 2 (SMAD2), 43 suggesting a negative feedback loop in which RA made by adipose resident stromal cells inhibits adipocyte proliferation by maintaining TGF‐β‐producing Mϕs 44 . Consistent with this idea, the CD206 + Mϕs in epididymal fat inhibit the growth and differentiation of adipocyte progenitors, thereby preserving adipose tissue homeostasis 45 .…”
Section: Innate Immunity In the Peritoneal Cavity And Omentummentioning
confidence: 99%